Alternating group actions on spin 4-manifolds - Li, Hongxia; Liu, Ximin (Mathematica Scandinavica, 2008)
Let X be a smooth, closed, connected spin 4-manifold with b_1(X)=0 and non-positive signature σ(X). In this paper we use Seiberg-Witten theory to prove that if X admits a spin alternating A_5 action, then b_2^+(X)≥ |σ(X)|/8 +3 under some non-degeneracy conditions.